Spread of airborne antibiotic resistance from animal farms to the environment: Dispersal pattern and exposure risk - Hong Bai; Liang-Ying He; Dai-Ling Wu; Fang-Zhou Gao; Min Zhang; Hai-Yan Zou; Mao-Sheng Yao; Guang-Guo Ying (Environment International, 2022)
Animal farms have been considered as the critical reservoir of antibiotic resistance genes (ARGs) and antibiotic resistant bacteria (ARB). Spread of antibiotic resistance from animal farms to the surrounding environments via aerosols has become a growing concern. Here we investigated the dispersal pattern and exposure risk of airborne ARGs (especially in zoonotic pathogens) in the environment of chicken and dairy farms. Aerosol, dust and animal feces samples were collected from the livestock houses and surrounding environments (upwind and downwind areas) for assessing ARG profiles. Antibiotic resistance phenotype and genotype of airborne Staphylococcus spp. was especially analyzed to reveal the exposure risk of airborne ARGs. Results showed that airborne ARGs were detected from upwind (50 m/100 m) and downwind (50 m/100 m/150 m) air environment, wherein at least 30% of bacterial taxa dispersed from the animal houses. Moreover, atmospheric dispersion modeling showed that airborne ARGs can disperse from the animal houses to a distance of 10 km along the wind direction. Clinically important pathogens were identified in airborne culturable bacteria. Genus of Staphylococcus, Sphingomonas and Acinetobacter were potential bacterial host of airborne ARGs. Airborne Staphylococcus spp. were isolated from the environment of chicken farm (n = 148) and dairy farm (n = 87). It is notable that all isolates from chicken-related environment were multidrug-resistance (>3 clinical-relevant antibiotics), with more than 80% of them carrying methicillin resistance gene (mecA) and associated ARGs and MGEs. Presence of numerous ARGs and diverse pathogens in dust from animal houses and the downwind residential areas indicated the accumulation of animal feces origin ARGs in bioaerosols. Employees and local residents in the chick farming environment are exposed to chicken originated ARGs and multidrug resistant Staphylococcus spp. via inhalation. This study highlights the potential exposure risks of airborne ARGs and antibiotic resistant pathogens to human health.